Effects of Oral Liposomal Glutathione in Altering the Immune Responses Against Mycobacterium tuberculosis and the Mycobacterium bovis BCG Strain in Individuals With Type 2 Diabetes - To, Kimberly; Cao, Ruoqiong; Yegiazaryan, Aram; Owens, James; Nguyen, Timothy; Sasaninia, Kayvan; Vaughn, Charles; Singh, Mohkam; Truong, Edward; Medina, Albert; Avitia, Edith; Villegas, Jose; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The World Health Organization (WHO) has identified type 2 diabetes (T2DM) as a neglected, important, and re-emerging risk factor for tuberculosis (TB), especially in low and middle-income countries where TB is endemic. In this clinical trial study, oral liposomal glutathione supplementation (L-GSH) or placebo was given to individuals with T2DM to investigate the therapeutic effects of L-GSH supplementation. We report that L-GSH supplementation for 3 months in people with T2DM was able to reduce levels of oxidative stress in all blood components by increasing levels of glutathione (GSH). Additionally, L-GSH supplementation significantly reduced the burden of intracellular mycobacteria within in vitro granulomas generated from peripheral blood mononuclear cells (PBMCs) of T2DM subjects. L-GSH supplementation also increased the levels of Th1-associated cytokines, IFN-γ, TNF-α, and IL-2 and decreased levels of IL-6. In conclusion, oral L-GSH supplementation in individuals with T2DM for three months was able to increase levels of GSH, reduce oxidative stress, and increase the levels of Th1-associated cytokines IFN-γ, TNF-α, and IL-2, resulting in an improved ability to control the in vitro mycobacterial infection.